Evaluation Of Cost And Time Performance Control Using The Concept Method Of Earned Value In The Purwodadi Market Development Project, Argamakmur District, North Bengkulu Regency - Muhammad Anwar; Endah Kurniyaningrum; Darmawan Pontan; Innavona Innavona (Green Publisher Indonesia, 2024)
Construction projects often face challenges in maintaining a balance between execution and planning, especially in terms of time and cost. Delays and cost overruns often hinder project efficiency, which has an impact on the satisfaction of the project owner. This study aims to evaluate the cost and time performance of the Purwodadi Market development project in North Bengkulu Regency using the Earned Value Management (EVM) approach. The EVM method was chosen because of its ability to provide a comprehensive picture of the achievement of project performance in terms of time and cost. Data is obtained from the project's weekly report and analyzed using indicators such as Actual Cost of Work Performed (ACWP), Budgeted Cost of Work Scheduled (BCWS), and Budgeted Cost of Work Performed (BCWP). The results show that in the 9th month, the project achieved faster progress than scheduled with a Schedule Performance Index (SPI) of 1.068 and a Cost Performance Index (CPI) of 1.012. This shows that the project is running more efficiently in terms of time and more cost-effective compared to the planned budget. However, there are several months before (the 5th to 8th month) that show delays and wasted costs. The conclusion of this study is that the EVM method is effective in evaluating project performance and allows for the identification of areas that need improvement. Thus, the application of EVM is recommended to improve the management efficiency of similar construction projects.